RETURN SAHAM, INFLASI, DAN STRUKTUR KEPEMILIKAN TERHADAP RISIKO INVESTASI - Siti Komariah; Julenah Julenah; M. Chudori (Jurnal Keuangan dan Perbankan, 2011)
The economic crisis in Indonesia had an impact on the declining performance of the companys fundamentalson the stock market. This degradation was caused by a failure in risk management, especially the unsystematicrisk. Many companies could not manage their debt policy, investment decision, earnings management,liquidity, and ownership structure that had implications for the risk. The objective of this research was toinvestigate the effect of stock return, inflation and ownersip stucture to investment risk of manufacturerindustries in 2003-2009. Population of this research was manufacturing companies listed in BEI. The samplingmethod used in this research was purposive sampling and the results were 126 companies based on thecriteria of the sample. Polling data method and judgment sampling were used to collect the data and two stageleast squares (2 SLS) were as the analysis method. Based on the hypothesis test, it could be summarized that allpredictors had a significant effect simultaneously. Result of the 1st model showed that only investment andprofitability effect to stock return partially ; 2nd model, SBI, KURS, and M2 had an effect to the inflationpartially; 3rd model was only dividend payout ratio and debt to equity ratio effected to ownership structurepartially ; 4th model showed that only return variable significantly influenced to investment risk partially